2011
DOI: 10.18517/ijaseit.1.2.30
|View full text |Cite
|
Sign up to set email alerts
|

Assistive Courseware for Hearing Impaired Learners in Malaysia

Abstract: This paper reports a research on Hearing Impaired (HI) learners in Malaysia which focuses on beginner level. This research has been carried out with intention to solve problem faced by parents of HI children in teaching their children to know the six basic sounds which is known as Ling-6 Sound. The HI learners were assisted by speciallydeveloped electronic-learning application or known as Assistive Courseware (AC) in their teaching and learning process. The AC utilizes their mother tongue language. The objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…: Amoah-Abban, 2017: Mac-Berango, 2017:Ariffin et al, 2018: Nwanekezie and Nwangunia, 2019).However, providing accommodation and hideouts for criminals with a mean value of 3.84 were ranked 3 rd and overall 6 th position.The following researchers have confirmed the above results(Abdul and Omran, 2011: Olulusi and Otunola, 2012: Amoah-Abban, 2017: Ariffin et al, 2018: Nwanekezie and Nwangunia, 2019 in their various studies. The owner and the populace have a mean value of 3.68 with a ranking of 4 th position.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…: Amoah-Abban, 2017: Mac-Berango, 2017:Ariffin et al, 2018: Nwanekezie and Nwangunia, 2019).However, providing accommodation and hideouts for criminals with a mean value of 3.84 were ranked 3 rd and overall 6 th position.The following researchers have confirmed the above results(Abdul and Omran, 2011: Olulusi and Otunola, 2012: Amoah-Abban, 2017: Ariffin et al, 2018: Nwanekezie and Nwangunia, 2019 in their various studies. The owner and the populace have a mean value of 3.68 with a ranking of 4 th position.…”
supporting
confidence: 54%
“…Previous researchers like (Efemudu, 2010: Ihauh and Benebo, 2014: Abdul Rahman et al, 2016: Amoah-Abban, 2017: Ariffin et al, 2018: Nwanekezie and Nwangunia, 2019 have confirmed these results in their various studies that loss of total income receivable from the real property was critical impact factor of project abandonment. A decrease in revenue accruable to the state as an impact of completed project abandonment has been identified in the previous studies conducted by (Abdul and Omran, 2011: Ihauh and Benebo, 2014: and Damoah, 2015. Waste of material and human resources with a mean score value of 3.71 has an impact on the economic condition of the country with a rank of 6 th and an overall position of 14 th .…”
Section: Stakeholders Ranking Results Of Impacts Of Completed Project...mentioning
confidence: 86%
See 1 more Smart Citation
“…First, previous studies on the development of ICT-based learning resources for deaf students namely, (1) [22] developed e-learning design or courseware based on multiple intelligence theory for learning sign language for beginners, (2) [23] developed sign language courseware for 7-8 years old deaf students. The results found that courseware can help teachers, students, and parents in teaching and learning sign language.…”
Section: Introductionmentioning
confidence: 99%
“…A. (2018) (Aziz et al, 2011;Saud & Nasruddin, 2016;Dawis, 2013;Gunawan & Salim, 2013). Several other researchers have also tried to develop interactive media for subjects such as (1) Effendi (2016) who has developed interactive learning media for science learning, and (2) Marzal (2014) who has developed interactive media for English lessons.…”
Section: Discussionmentioning
confidence: 99%